SAYAP SEBAGAI REPRESENTASI PATUNG KINETIK - Lutse Lambert Morin (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
One type of artwork that is three-dimensional is sculpture. The forms to be developed in this creation are various forms of sculptures that represent animal wings using industrial materials, namely car and motorcycle engines. The choice of wing shape is based on the author’s interest in the movement of animal wings that have rhythm and beauty of motion. Wings become an important part of winged animals such as birds and insects. It is these wings that carry them foraging, breeding and living. Through the qualitative approach method with the Research (DBR) method, the author tries to realize aesthetically pleasing three-dimensional artworks with industrial materials. Industrial materials in the form of car engines are assembled into kinetic sculptures that represent the shapes of animal wings. This study aims to conduct experiments combining waste motorcycles and used cars, screws and household tools into sculpture works using welding raft and screw techniques. In addition, this research is also to realize aesthetic ideas and ideas according to empirical abilities and experiences expressed in the form of three-dimensional works.